2013
DOI: 10.3797/scipharm.1301-16
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of a Polyphenolic Fraction of Cinnamomum zeylanicum L. bark in Animal Models of Inflammation and Arthritis

Abstract: Cinnamon bark (Cinnamomum zeylanicum Syn C. verum, family: Lauraceae) is one of the oldest traditional medicines for inflammatory- and pain-related disorders. The objective of the present study was to evaluate the efficacy of the polyphenol fraction from Cinnamomum zeylanicum bark (CPP) in animal models of inflammation and rheumatoid arthritis. Dose-response studies of CPP (50, 100, and 200 mg/kg) used in a separate set of in vivo experiments were conducted in acute (carrageenan-induced rat paw edema), subacut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 64 publications
1
35
0
1
Order By: Relevance
“…Cinnamon bark ( Cinnamomum zeylanicum ), one of the most common spices used in Indian, Bangladeshi, Burmese, and Sri Lankan dishes, can confer some protective effects against RA. Rathi et al [ 189 ] observed a significantly ( p < 0.001) higher level of anti-inflammatory activities [inhibition of cytokines (IL-2, IL-4, and IFN- γ ) and reduction of TNF- α concentration] upon the treatment of RA animal models (male Wistar rat and Swiss albino mice) with the polyphenolic fractions of cinnamon bark.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Cinnamon bark ( Cinnamomum zeylanicum ), one of the most common spices used in Indian, Bangladeshi, Burmese, and Sri Lankan dishes, can confer some protective effects against RA. Rathi et al [ 189 ] observed a significantly ( p < 0.001) higher level of anti-inflammatory activities [inhibition of cytokines (IL-2, IL-4, and IFN- γ ) and reduction of TNF- α concentration] upon the treatment of RA animal models (male Wistar rat and Swiss albino mice) with the polyphenolic fractions of cinnamon bark.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…[14] Since ages, the importance of several medicinal plants has been mentioned in the treatment of diabetes. One such plant is Cinnamomum zeylanicum (family-Lauraceae), has shown numerous pharmacological properties, such as anti-inflammatory, [15] antiarthritic, [16] antimicrobial, [17] and antioxidant [18] activities. In vitro and in vivo antidiabetic studies on C. zeylanicum bark have shown to promote insulin receptor phosphorylation, insulin signaling, and enhancing IS.…”
Section: Original Articlementioning
confidence: 99%
“…[51] In another study, C. zeylenicum extract was found to reduce inflammation and arthritis in rats by suppressing intracellular release of TNF-α in dose-dependent manner and; hence is an effective remedy for treating RA. [52,53] …”
Section: Guggulosteronementioning
confidence: 99%